Pengaruh Recruitment dan Pengembangan Karyawan terhadap Kinerja Kerja Karyawan (Studi Kasus pada Perum Bulog Subdivre Lampung Tengah) - Pratama, Hendri; Lelawati, Nina (Jurnal Manajemen DIVERSIFIKASI, 2021)
Employee work performance is the result achieved by a person both in quality and quantity according to the responsibility given to him. The formulation of the problem in this study is "Does the recruitment and employee development simultaneously affect the work performance of employees in Bulog Subdivre Central Lampung". From these problems, the purpose of this study is to determine the effect of recruitment and employee development simultaneously on the work performance of employees in Bulog Subdivre Central Lampung. This research method is quantitative. Teknik used in this research data collection used observation, wawancara and questionnaires. Later in the data analysis used quantitative methods, namely kemudian analyzed data collected. After the data is collected, then the data is analyzed using multiple regression analysis and processed using SPSs. Based on data analysis using SPSS, the conclusions of the recruitment and development of employees have significant together with the performance of employees at Perum Bulog Subdivre Central Lampung.